Prehypertension and its associated factors among government employees in Tilottama Municipality of Rupandehi District, Nepal - Sheetal Bhandari; Paras Kumar Pokharel; Ashmita Maharjan; Manish Rajbanshi; Kshitij Kunwar; Jwala Subedi; Anup Poudel; Suman Bahadur Singh; Vijay Kumar Khanal; Gyanu Nepal Gurung (PLoS ONE, 2025)
Government employees are vital workforce of the nation comprising individuals in the working age group. These employees have to face an increased workload, limited decision-making scope, lack of support from fellow workers, regular night shifts, limited physical mobility which puts them at increased risk for hypertension. Detecting prehypertension is essential to prevent related complications and reduce risks of future health issues such as an increased risk of developing high blood pressure (hypertension), heart disease, stroke, kidney damage, and other cardiovascular problems. This study aimed to assess the prevalence of prehypertension and its associated factors among the government employees of Tilottama Municipality, Nepal. A cross-sectional study was conducted among 333 government employees from 15 June 2023 to 10 November 2023. A systematic random sampling technique was used to select participants. A structured questionnaire was adapted from the WHO STEPs Survey. Data were cleaned and then exported to IBM SPSS Statistics 20.0 for analysis. Demographic characteristics of respondents were described using descriptive statistics. Multivariate logistic regression was conducted to determine the association between individual characteristics and prehypertension. Statistical significance was set at p-value < 0.05. The mean (±SD) age of the 333 participants was 36.9(±8.89) years. Most of them were females (54.1%). This study found that 29.4% of participants were prehypertensive, and 14.1% were hypertensive. Participant’s age, sex, working department, family history of hypertension, presence of diabetes, BMI, waist-hip ratio, ever-alcohol consumption and duration of service were found to be significantly associated with prehypertension in bivariate analysis. Meanwhile, working department (Adjusted Odds Ratio AOR: 3.2, CI: 1.4–7.0), family history of hypertension (AOR: 1.9, CI: 1.1–3.4), and BMI (AOR: 1.7, CI: 1.0–3.1) were found to be significantly associated with prehypertension. This study concluded that a significant proportion of government employees had prehypertension and hypertension. Targeted health promotion programs should be implemented in non-health departments. Regular hypertension screening program and healthy workplace settings such as healthier food choices, physical activity, stress management techniques, and smoke-free zones should be promoted in each institution, with a focus on hypertension prevention and control for employees.